Disease spectrum and prognostic factors in patients treated for tuberculous meningitis in Shaanxi province, China - Wang, Ting; Li, Meng-yan; Cai, Xin-shan; Cheng, Qiu-sheng; Li, Ze; Liu, Ting-ting; Zhou, Lin-fu; Wang, Hong-hao; Feng, Guo-dong; Marais, Ben J.; Zhao, Gang (Frontiers in Microbiology, 2024)
Background: Tuberculous meningitis (TBM) is the most severe form of tuberculosis (TB) and can be difficult to diagnose and treat. We aimed to describe the clinical presentation, diagnosis, disease spectrum, outcome and prognostic factors of patients treated for TBM in China. Methods: Multicenter retrospective study conducted from 2009-2019 enrolling all presumptive TBM patients referred to Xijing tertiary Hospital, from 27 referral centers in and around Shaanxi province, China. Patients with clinical features suggestive of TBM (abnormal CSF parameters) were included in the study if they had adequate baseline information to be classified as “confirmed”, “probable”, or “possible” TBM according to international consensus TBM criteria and remained in follow-up. Patients with a confirmed alternative diagnosis or severe immune compromise were excluded. Clinical presentation, central nervous system imaging, cerebrospinal fluid (CSF) results, TBM score and outcome - assessed using the modified Barthel disability index - were recorded and compared. Findings: A total of 341 presumptive TBM patients met selection criteria; 63 confirmed TBM (25 culture positive, 42 Xpert-MTB/RIF positive), 66 probable TBM, 163 possible TBM and 49 “not TBM”. Death was associated with BMRC grade III (OR=5.172; 95%CI:2.298-11.641), TBM score ≥ 15 (OR=3.843; 95%CI:1.372-10.761), age >60 years (OR=3.566; 95%CI:1.022-12.442), and CSF neutrophil ratio ≥ 25% (OR=2.298; 95%CI: 1.027-5.139). Among those with confirmed TBM, nearly a third (17/63; 27.0%) had a TBM score <12; these patients exhibited less classic meningitis symptoms and signs and had better outcomes compared to those with a TBM score ≥ 12. In this group, signs of disseminated/miliary TB (OR=12.427; 95%CI: 1.138-135.758) and a higher TBM score (≥15, OR=8.437; 95%CI: 1.328-53.585) were most strongly associated with death. Conclusion: TBM patients that are older (>60 years), have higher TBM scores or CSF neutrophil ratios, or have signs of disseminated/miliary TB, are at greatest risk of death. In general, more needs to be done to improve early diagnosis and treatment outcome in TBM patients.